2016
DOI: 10.1038/nmicrobiol.2016.93
|View full text |Cite
|
Sign up to set email alerts
|

Colonic transit time is related to bacterial metabolism and mucosal turnover in the gut

Abstract: Little is known about how colonic transit time relates to human colonic metabolism and its importance for host health, although a firm stool consistency, a proxy for a long colonic transit time, has recently been positively associated with gut microbial richness. Here, we show that colonic transit time in humans, assessed using radio-opaque markers, is associated with overall gut microbial composition, diversity and metabolism. We find that a long colonic transit time associates with high microbial richness an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

31
307
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 358 publications
(342 citation statements)
references
References 67 publications
31
307
1
3
Order By: Relevance
“…6, Inset). Furthermore, microbiome sequencing has confirmed nutrient inflow, transit time, and water content to be crucial determinants of microbiota composition (31,32,45,46), with stool consistency (BSS) identified as the single most important factor explaining microbiota variation in a large-scale epidemiological study (44). Our results offer a minimal explanation for these variations: Nutrient inflow and stool consistency affect microbiota composition via changes in luminal pH.…”
Section: Discussionmentioning
confidence: 66%
“…6, Inset). Furthermore, microbiome sequencing has confirmed nutrient inflow, transit time, and water content to be crucial determinants of microbiota composition (31,32,45,46), with stool consistency (BSS) identified as the single most important factor explaining microbiota variation in a large-scale epidemiological study (44). Our results offer a minimal explanation for these variations: Nutrient inflow and stool consistency affect microbiota composition via changes in luminal pH.…”
Section: Discussionmentioning
confidence: 66%
“…The modulating effect of specific growth rate on the colon microbiota is not understood, yet, however, it can be assumed that faster transit supports fast-growing bacteria and vice versa . Roager et al showed that long transit time is associated with higher abundances of Methanobrevibacterium and certain taxa from Ruminococcaceae and Christensenellaceae in adult fecal microbiota [4]. Despite the significance of the transit time, this parameter is difficult to measure in practice.…”
Section: Discussionmentioning
confidence: 99%
“…The fibers that are only partially or non-fermented by the gut microbiota increase the fecal volume and transit rate by binding to water. Peristalsis, water absorption, environmental acidity, redox potential, and the absorption of nutrients are affected by the intestinal microbiota, and in turn, affect the microbiota as well [3,4]. Hence, short bowel transit time (below 24 h) might support the fast-growing bacteria and can be a key factor to control the fermentation of dietary fibers in the colon.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood levels of these toxins (e.g., p-cresol sulfate, indoxyl sulfate) increase when kidney function declines (16), and higher levels are directly associated with higher dietary protein and lower fiber intakes (41). Colonic transit time (i.e., the time it takes for digesta to move through the colon) also significantly impacts the gut microbiota and fermentation (40). Slow transit, commonly referred to as constipation, increases protein fermentation due to depletion of carbohydrate substrate (49).…”
mentioning
confidence: 99%